Contemporary Brazil : issues in economic and political development - Rosenbaum, H. Jon; Tyler, William G. (New York : Praeger, 1972)
This book provides a details and often technical discussion of a significant development issue or problem which had confronted Brazil during the past ten years. (Between 1962-1972)
Includes bibliographical references.
oo 12/09/2018
Loans
Keywords: Political economy; Brazil